Global Ethics for a Failed World - The renaissance of political Confucianism in contemporary China - Matten, Marc (Universal Values in a post-secular Era, 2016)
Post-revolutionary China has witnessed a profound crisis not only in terms of ideology̶replacing socialism with patriotism̶but also in terms of ethics. Corruption, the crime rate, exploitation, prostitution, and consumerism have increased to an unexpected extent since the revival of capitalism. This has led to new ideological creations such as the Harmonious Society and the Chinese Dream, coupled with populist campaigns such as the Strike-Hard campaigns against crime and others. A closer look at the uncountable social problems, however, shows that ideology alone is unable to ease the existing conflicts. This has caused many social and political groupings to encourage a return to Confucian values, which are not only supposed to foster a sense of national and cultural pride in China, but are also viewed as a legitimate and powerful contribution to global political philosophy. The current debates on the role of Confucianism are, however, not able to provide an answer as to how these aims will be achieved, let alone if and to what extent these values are actually able to provide a new orientation to both the winners and losers of modernization.